Reconceiving pasts in a digital age - Tanaka, Stefan (Historein, 2016)
This essay explores the way that digital media helps us think differently about how we practice history. Digital media can raise two issues about how our current practices can offer new ways to explore the current state of historiography. First, the more one is immersed in digital tools, they make us question first principles, the various practices and assumptions of modern history itself. Second, it offers ways of communicating the past that do not hide the process of “doing” history. In this article I will draw on my project, 1884 Japan, to raise questions about data or the fact. By using recorded happenings, I plan to explore the distancing of fact from the context in which it was embedded. Recorded happenings exist prior to the filtering of importance. It enables us to first recover the heterogeneity of pasts and recover the stories and experiences of a variety of people who have usually been written out of Japanese history. Second, by presenting this material I will suggest a layered, multitemporal history that combines the narrative of national becoming with the experiences of others.